Optimal pollen viability and vigor among varieties of Tagnanan Tall Coconut (Cocos nucifera L.) - Liew, Xi Yun; Ghazali, Mohd Norsazwan; Ismail, Mohd Firdaus; Abd Ghafar, Zarina; Isnar, Mohd Syarbani; Venkatachalam, Vasudevan; Sinniah, Uma Rani (The Scientific and Technological Research Council of Tuerkiye, 2024)
Controlled pollination, involving the transfer of pollen from Tagnanan Tall palm (male parent) to the Malayan Yellow or Red dwarf (female parent) is essential for producing MATAG coconut hybrids. However, the pollen from Tagnanan Tall (TAGT), used in hybridization, has been reported to have a germination percentage of less than 40%. This is further complicated by Tagnanan Tall varieties varying in color, TAGT Orange, TAGT Gold, and TAGT Green. TAGT Orange is claimed to have lower pollen viability than TAGT Gold and Green. Hence, a study was conducted to compare inflorescence characteristics, pollen yield, size, viability, and vigor of three Tagnanan tall (TAGT) cultivar. The best-performing cultivar was used to compare pollen viability at different positions on the rachis and rachilla. The results showed that pollen viability of TAGT Gold was 10% higher than TAGT Green and Orange. Pollen viability was influenced by the position of the male flower on the rachis. Pollen collected from the top and middle parts of the rachis (TMRS) had higher pollen vigor and achieved a viability of 61%, whereas mixing pollen from the whole inflorescence only resulted in 39% viability. Therefore, this study which aimed at optimizing pollen quality suggests that pollen should be harvested from the top and middle part of the rachis (TMRS).